The Nature of Certainty in Wittgenstein's On Certainty - McQuaid, Colin (My University, 2013)
In this thesis I examine the concept of certainty in the work of Ludwig Wittgenstein, with a focus on the collection of remarks entitled On Certainty. In the first part I examine two essays of G.E. Moore that initiated Wittgenstein’s discussion of certainty and critique of Moore’s two essays. As I show, Wittgenstein believes that Moore misunderstood the use of the expression of I know in relation to the propositions of common sense. Instead, Wittgenstein believes that the common sense propositions stand for a certainty that belongs to the language-game itself, a certainty that stands fast for everyone who participates in the language-game, like hinges on which the rest of our knowledge and doubt turn. The rest of my thesis is spent examining three different interpretations of this notion of hinge certainty. The first is hinges as presuppositions to combat skeptical arguments, offered by the philosophers Crispin Wright and H.J. Glock. The second is that hinges are Wittgenstein’s version of foundationalism, serving as the foundational framework of human language, a notion primarily advocated by the philosophers Avrum Stroll and Danièle Moyal-Sharrock. I then examine the interpretation of hinges as learned norms of judging and acting that we must display certainty in if we are to learn a language. This is the interpretation of Rush Rhees and Meredith Williams, and is the position that I support. Finally, I show that contrary to some the remarks in On Certainty express a unified theme, rather than a series of disjointed and contradictory ideas.
Keywords: Wittgenstein; Certainty; Hinges; Norms; Agreement; Knowledge; Foundationalism; Learning; Arts and Humanities; Arts and Humanities